Influence of precedents and fertilization level on winter wheat grain yield in the Left-Bank Forest-Step conditions - Hanhur, V.; Marenych, A.; Sokyrko, D. (Scientific Progress & Innovations, 2025)
The grain of winter wheat (Triticum aestivum L.) is a major agricultural raw material for the production of major foodstuffs. The world's constantly growing population and rising global wheat prices highlight the importance of fully ensuring this strategic resource. At the same time, it is impossible to increase grain harvest and improve grain quality without optimizing certain elements of technology, including fertilizer systems and finding the best position for the crops in the crop rotation. The study was conducted at the Poltava State Agricultural Research Station named after M. I. Vavylov during 2022–2024. The aim of the field experiment was to determine the effect of predecessors and fertilizer system on the formation of winter wheat productivity in short crop rotations. According to the results of the field experiment, was found that when growing winter wheat under conditions of unstable moisture in the Left-Bank Forest-Steppe of Ukraine, the best steam crop predecessors in crop rotations with a short rotation are black steam and sainfoin on one cutting. When the winter wheat was grown on these predecessors and mineral fertilizers were applied at the rate of N50P50K50, the yield of Niva Odessanska was 5.16 and 5.09 t/ha, respectively. According to the results of the research, it was noted that black steam as a predecessor of winter wheat in crop rotation was the most effective in terms of its effect on the biometric parameters of plants, the level of grain yield, in years with a deficit of available moisture in the soil both at the time of optimal sowing and during the growing season. In years with a moderate temperature regime and sufficient supply of moisture to plants, the effectiveness of black steam decreased and in terms of its impact on the conditions of winter wheat yield formation was comparable to non-steam predecessors. Among the non-fallow predecessors, it is advisable to locate winter wheat after cereals and soybeans. In crop rotations where winter wheat was sown after cereals and soybean, the yield of the crop was 4.77 and 4.65 t/ha, respectively, which is 7.6 and 9.9 % less than in the control (black fallow). It is undesirable to re-sow winter wheat in a crop rotation, where the negative impact of the predecessor is manifested even with the application of organic and increased doses of mineral fertilizers. As a result of this is a decrease in grain yield by 1.66 t/ha or 32.2 % compared to the placement of the crop on black fallow. The research showed that the sowing qualities of winter wheat seeds, in particular the weight of 1000 seeds and laboratory germination, remained almost unchanged depending on the predecessors in the crop rotation, except for the variant with re-sowing of wheat.